2015
DOI: 10.1530/jme-15-0213
|View full text |Cite
|
Sign up to set email alerts
|

Expression and functional studies of the GDNF family receptor alpha 3 in the pancreas

Abstract: The generation of therapeutic β-cells from human pluripotent stem cells relies on the identification of growth factors that faithfully mimic pancreatic β-cell development in vitro. In this context, the aim of the study was to determine the expression and function of the Glial cell line derived neurotrophic factor receptor α 3 (GFRα3) and its ligand Artemin in islet cell development and function. GFRα3 and Artn expression were characterized by in situ hybridization, immunochemistry and qRT-PCR. We used GFRα3-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…However, as shown in Fig. S5, Gfra3 was largely confined to endocrine cells as previously noted (Nivlet et al, 2016), and no difference between Hes1 −/− and controls was observed. Podocalyxin-like was found at the apical side of most epithelial cells, wherever a microlumen had formed, but again without a noticeable difference between Hes1 −/− and controls.…”
Section: Dorsal Pancreas Dysgenesis and Ectopic Pancreas Is Neurog3 Dsupporting
confidence: 79%
“…However, as shown in Fig. S5, Gfra3 was largely confined to endocrine cells as previously noted (Nivlet et al, 2016), and no difference between Hes1 −/− and controls was observed. Podocalyxin-like was found at the apical side of most epithelial cells, wherever a microlumen had formed, but again without a noticeable difference between Hes1 −/− and controls.…”
Section: Dorsal Pancreas Dysgenesis and Ectopic Pancreas Is Neurog3 Dsupporting
confidence: 79%